2021
DOI: 10.3390/plants10102057
|View full text |Cite
|
Sign up to set email alerts
|

The Exogenous Application of Micro-Nutrient Elements and Amino Acids Improved the Yield, Nutritional Status and Quality of Mango in Arid Regions

Abstract: The mango is one of the most valuable and appealing tropical fruits due to its color, aroma, tasteful remarkable flavor, and nutritive value; however, improving the yield and quality of mango is an urgent goal in order to combat global population growth. The application of amino acids and a micronutrient mixture might improve the yield and quality features but further research is still required in arid regions. To study the combined effect of a micronutrient mixture (MM) and amino acids (AA) at different rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The purpose of developing nanoparticle fertilizers is to effectively deliver required nutrients to plants while not adding large amounts of fertilizer to the environment [25]. In agriculture, nanotechnology has been studied to reduce the use of reactive chemicals, reduce nutrient losses, and increase economic crop yields through precise nutrient management [26], followed by micronutrients and amino acids [27]. Other studies found that application of nanoparticles (NPs) enhanced iron content, redox, growth, and yield of B. juncea [28]; improved growth, yield, and quality of rice [29]; improved the biological activities of sweet basil [30].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of developing nanoparticle fertilizers is to effectively deliver required nutrients to plants while not adding large amounts of fertilizer to the environment [25]. In agriculture, nanotechnology has been studied to reduce the use of reactive chemicals, reduce nutrient losses, and increase economic crop yields through precise nutrient management [26], followed by micronutrients and amino acids [27]. Other studies found that application of nanoparticles (NPs) enhanced iron content, redox, growth, and yield of B. juncea [28]; improved growth, yield, and quality of rice [29]; improved the biological activities of sweet basil [30].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of PHs increased the leaf area and the yield of some fruit trees and other horticultural plants [78][79][80]. In this respect, the available literature data highlight a positive effect of the PHs' application, isolated AAs (proline, tryptophan) or mixtures of AAs (alone or combined with micronutrients) on flowering regulation, fruiting, and fruit quality [81][82][83][84][85][86]. For instance, application of an animal-derived PH (enzymatic hydrolysates obtained from animal hemoglobin) resulted in earlier flowering, and in a significant increase in early fruit production in cold-stressed strawberry plants [87].…”
Section: Shoot Biomass and Yieldmentioning
confidence: 99%